The Relationship between the Science of Qur’anic Readings and Grammatical Studies and Their Impact on the Interpretation of the Holy Qur’an – Selected Examples from Surah Al-Baqarah - laouidji, Ahmed (El Omda in Linguistics and Discourse Analysis, 2025)
Quranic readings are one of the sources of language that have enriched the Arab linguistic corpora, and were and still a solid support for deriving the rule in many grammatical issues. They’ve been taken as evidences for the standardization of Arabic in Basirite and Kufic schools and at different degrees of support and attribution, according to the principles of each school either transmission or exception. So, they’ve contributed, in a way or another, to construct the grammatical lesson and to rectify some of its aspects. This relationship between the two sciences has played a prominent role in interpreting Quranic verses. On this basis, this paper comes to: - Monitoring the intersections between Quranic readings science and grammar and interpretation sciences, and tracing the forms of integration between them. - Demonstrating the need of these sciences to one another for their construction, growing and sustainability. Keyw